PREVALENCE OF JAUNDICE BASED ON LIVER FUNCTION TEST IN WESTERN NEPAL - Singh, P.; Khan, S.; Mittal, and R. K. (BALI MEDICAL JOURNAL; Volume 2 Number 2, May-August 2013, 2013)
Objectives: The aim of this study was to evaluate the Prevalence of Jaundice Based on Liver Function Test in Patients Attending OPD of Nepalgunj Medical College and Teaching Hospital. Materials and Methods: A hospital based study was carried out in Nepalgunj Medical College, Kohalpur, Banke Nepal to determine prevalence of jaundice. A total of 4280 subjects females and males were included in this study. The study took place from February 2012 to January 2013. Liver function tests were performed using serum levels of bilirubin, total protein,  albumin,  serum  glutamate oxaloacetate transaminase  (SGOT),  serum glutamate pyruvate  transaminase  (SGPT), and alkaline phosphatase (ALP) as indicators of liver function .The results obtained from the above investigation were analyzed and expressed as mean ± SD by using Excel 2007. The comparison was done by student t test on no. of variable of each parameter using SPSS version 16. Results: We investigated the prevalence of jaundice in 4280 subjects on the basis of liver function test. Out of 4280 subjects, 152 patients (3.55%) were selectively diagnosed as jaundiced and another 152 healthy individuals have taken as control. The serum concentrations of all the parameters of liver function test in jaundiced patients were significantly higher (p<0.0001) than those of controls except total protein and albumin which was significantly lower in (p<0.0001) experimental group than the control group. Conclusions: Therefore, from the trend of our data, we can conclude that liver dysfunction is a very common feature in the population of western part of Nepal this may be due most of the people are addicted to alcohol consumption. This need to be stopped and continuous surveillance for bilirubin test is very important to diagnose the jaundice.
Keywords: Prevalence, Liver function test, Jaundice